Analysis of Financial Health Level Using the Z-Score (Altman) Method in Transportation Companies Listed on the Indonesia Stock Exchange for the 2019-2021 Period - Ahmadi Aidi; Tri Wahyudi Setiawan; Ahmad Junaidi; Agus Budiwaluyo; Redjeki Agoestyowati (Yayasan Ilomata, 2022)
This study aims to determine the company's financial condition based on the Altman (Z-Score) method and the effect of the ratio of Working Capital to Total Assets, Retained Earning to Total Assets, Earning Before interest and tax to Total Assets and Market Value of Equity to Book Value of Debt on the company's financial soundness (Altman Z-score). The population in this study is the transportation sector listed on the Indonesia Stock Exchange for the period 2019-2021. Sampling in this study was to use the purposive sampling method so as to obtain a sample of 36 from 12 companies. The data used in this study is the company's annual financial statements obtained from the Indonesia Stock Exchange. The data is then grouped and entered into the Altman Z-score formula and analyzed using the multiple linear regression method using the SPSS version 23 program. The results from the Altman Z-score show that in 2019 there were 5 companies in good health, 4 companies in an emergency (grey area) and 3 companies in a potentially bankrupt condition. In 2020 there are 6 companies in good health, 4 companies in an emergency (grey area) and 2 companies in a potentially bankrupt condition. In 2021 there are 6 companies in good health, 3 companies in an emergency (grey area) and 3 companies in a potentially bankrupt condition. Meanwhile, the results of the analysis test show that the variables Working Capital to Total Assets, Retained Earning to Total Assets, Earning Before Interest and Tax to Total Assets and Market Value Of Equity to Book Value Of Debt, individually and jointly significant effect the level of financial health of the company (Altman Z-score).